No free lunch for large investors - Peter Bank (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
We study an extension of the classical B1ack-Scholes model which accounts for feedback effects from trading in an imperfectly elastic market. The proposed semi-martingale model may be viewed as a compromise between the diffusion approach in, e.g., (Cuoco and Cvitanic 1998), (Cvitanic and Ma 1996) and the reaction function framework used in, e.g., (Jarrow 1992), (Frey and Stremme 1997). We motivate our model by a discrete-time approximation and provide sufficient conditions which exclude arbitrage opportunities for large investors.
urn:nbn:de:kobv:11-10046980
Keywords: G12; 330; large investor; feedback effect; no arbitrage; illiquid markets; market elasticity